STRENGTHENING STUDENTS’ ISLAMIC VALUES THROUGH ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING AND RELIGIOUS HABITUATION AT SMK 1 RAUDLATUL AL FALAH PROBOLINGGO - Maulida, Ifa; Nufus, Lailatun; Nisa’, Choirun; Wicaksono, Jihan Nabila; Khadavi, M Jadid (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study examines the synergy between Islamic Religious Education (PAI) learning and religious habituation in strengthening students’ Islamic values at SMK 1 Raudlatul Al Falah Probolinggo. Employing a qualitative approach with a case study design, the research collected data through in-depth interviews with students, PAI teachers, and the school principal, as well as systematic observations of religious habituation activities conducted within the school environment. The findings reveal that the integration of formal PAI instruction with consistent religious practices greatly enhances students’ cognitive understanding, emotional awareness, and behavioral internalization of Islamic teachings. Religious habituation programs—such as congregational prayer, Qur’an recitation, morning dhikr, and faith-based social activities—serve as effective reinforcement mechanisms that help shape students’ moral character, discipline, and spiritual awareness. Students reported noticeable improvements in religious commitment and social behavior, including increased honesty, empathy, responsibility, and mutual respect. The study also highlights how supportive school culture, teacher role modeling, and collaborative involvement of stakeholders contribute significantly to the success of this integrative approach. Overall, the synergy between PAI learning and religious habituation proves to be a strategic model for cultivating strong Islamic values and fostering holistic religious character development among vocational high school students.